MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS DAN KARAKTER WASAKA PADA MUATAN IPAS MENGGUNAKAN MODEL PBL, NHT, TALKING STICK TERINTEGRASI STEAM PADA SISWA SEKOLAH DASAR - Sarwani Abdan; Muhsinah Annisa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is focused on improving critical thinking skills and also the character of Wasaka (diligent) students through Problem Based Learning, Number Head Together, and Talking Stick which is integrated with STEAM in learning IPAS. This research was carried out in the form of Class Action Research (PTK) with a qualitative approach, which was divided into two cycles. in grade V of elementary school. Data collection used observation sheets as the main instrument to assess critical thinking skills and Wasaka (diligent) character. Indicators of critical thinking include interpretation, analysis, evaluation, and inference. Meanwhile, Wasaka character indicators (diligent) include the attitude of working hard, being earnest, respecting time, and completing tasks. The results showed that students' critical thinking skills increased from 60% in cycle I to 90% in cycle II. Wasaka's character (diligent) has also increased from 55% to 90%. The learning model applied creates a collaborative and fun learning atmosphere, so it is effective in encouraging the development of students' critical thinking skills and character.